Scholarship on Trans-Himalayan (Tibeto-Burman) languages of South East Asia - Hill, Nathan (Mouton de Gruyter, 2021)
The spread of the Trans-Himalayan family¹ naturally paid no attention to 21st century political boundaries. The family includes languages with a geographic range from Balti Tibetan in Pakistan to Hokkien Chinese in Indonesia,with the foothills of the Himalyas and the South East Asian highlands as its center of gravity. Van Driem (2001) and Thurgood (2017a) provide helpful introductions to the family overall. Here we restrict the focus to South EastAsia, in more specific terms treating those Trans-Himalayan branches that include languages spoken in today’s Myanmar and Thailand and excluding Chinese. I include discussion of subbranches entirely contained within the boundaries of the Peoples Republic of China (Rgyalrongic, Qiangic, Ersuic, and Naish), but omit treatment of primary branches entirely confined to regions under the control of China, India, Nepal or Bhutan (Bai, Tujia, Kiranti,etc.); these criteria yield Burmo-Qiangic, Kuki-Chin, Karen, Sal, Mruic, and Nungish as the branches for discussion. The farther South and East a language is spoken, the more it exhibits the typical South East Asian typological profile of simple syllable structure, lack of inflection, and concatenating auxiliary verbs. Karenic,as the most southern of the Trans-Himalyan subgroups, reflects the vanguard of this transition, whereas the Rgyalrongic languages of Sichuan exhibit the opposite extreme. The frequency of the South East Asian typology in the Trans-Himalayan family is what led Meillet to despair that “la restitution d’une « langue commune » dont le chinois, le tibétain, etc., par example,seraient des formes postérieures,se heurte à des obstacles quasi invincibles”(1954, 26-27). Such pessimism is not entirely warranted. On the one hand, historical linguistics is still profitably undertaken even in such innovative branches as Naic (Jacques and Michaud 2011) and Karenic (Haudricourt 1946; Haudricourt 1975). On the other hand, Kuki-Chin, Sal, Mruic, and Nungish all have inflectional morphology of the kind that has facilitated progress in the reconstruction of Indo-European. As data on more languages become available, it is increasingly clear that the typological profile of the Trans-Himalayan proto-language is close to that of the Rgyal-rongic languages, with complex syllable structure and ornate inflection; the more typically South East Asian languages have lost these features more or less independently. While it is inappropriate to speculate too precisely about prehistoric migrations on the basis of language distributions today, without the corroborating evidence of genetics or archaeology (pace LaPolla 2012), the broad pattern–languages with complex syllable structure and abundant inflectional morphology spoken in more mountainous terrain contrasting with languages of more simple structure spoken in flatter and more southern regions–points to an Urheimat inside of what is now China. The Lolo-Burmese seem to be a relative newcomer to South East Asia, with Nungish, Sal, Kuki-Chin, and Karen having spread earlier.
The Languages and Linguistics of Mainland Southeast Asia
PUBLISHED
Berlin
Keywords: Identities in Transformation; Asian languages